2023
DOI: 10.11591/ijece.v13i2.pp2156-2166
|View full text |Cite
|
Sign up to set email alerts
|

A review of the automated timber defect identification approach

Abstract: Timber quality control is undoubtedly a very laborious process in the secondary wood industry. Manual inspections by operators are prone to human error, thereby resulting in poor timber quality inspections and low production volumes. The automation of this process using an automated vision inspection (AVI) system integrated with artificial intelligence appears to be the most plausible approach due to its ease of use and minimal operating costs. This paper provides an overview of previous works on the automated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 68 publications
0
1
0
Order By: Relevance
“…Under this appellation, all knots, regardless of health, size, or shape, are included. In a study conducted in 2020 [39], machine learning techniques were employed to classify knots and cracks in oak, spruce, and TMT spruce-sawn timber within the wood industry. The findings indicated that a support vector machine (SVM) attained a defect identification accuracy of 75.8%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under this appellation, all knots, regardless of health, size, or shape, are included. In a study conducted in 2020 [39], machine learning techniques were employed to classify knots and cracks in oak, spruce, and TMT spruce-sawn timber within the wood industry. The findings indicated that a support vector machine (SVM) attained a defect identification accuracy of 75.8%.…”
Section: Resultsmentioning
confidence: 99%
“…The previously mentioned analysis [36] showed that the level of recognition of knots (sound and dead) is, on average, about 90% for the wood species Xyloma congestum. The majority of researchers focused on knots, as they are the most commonly encountered defect in timber, influencing both the structural integrity of the wood and the overall quality of the final product [39]. Additional improvements could be attained comparing the results obtained with the researched software.…”
Section: Resultsmentioning
confidence: 99%
“…In the last decade, several surveys and reviews focusing on image-based DL for industrial surface defects inspection have been published. However, the available works are either confined to a specialized application domain (such as metallurgical [18], [19], fabric and electronic [20], [21], [22], wood [23], and textile manufacturing [24], [25], [26]), or to a specific type of learning strategy (e.g., unsupervised methods [27]), or a specific architecture (e.g., Generative Adversarial Networks [28]), or else consider one single technique (e.g., transfer learning [29]) or requirement (e.g., lowering the number of labelled data for training [30]).…”
Section: B Paper Positioning In the Related Literaturementioning
confidence: 99%
“…In addition to the cited works [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], the related literature counts other reviews not specialised in the inspected material, employed architecture, or supervision level used for training. For instance, Czimmermann et al [31] explore visible and palpable defects and traditional feature extraction methods, characterizing supervised and unsupervised automatic approaches.…”
Section: B Paper Positioning In the Related Literaturementioning
confidence: 99%
“…Because of the rapid progress of technology, materials in factories are produced faster and faster. Flat surfaced products such as wood [5], fabric [6] and metal [7] require machine vision systems to detect production defects. Unfortunately, high-speed production of these goods combined with the availability of high-resolution cameras put great strain on the network and the computers that process those images in real time.…”
Section: Introductionmentioning
confidence: 99%